Analyses of Proximate Composition of Raw Urine of Some Female Camels (Camelus dromedarius) in Sokoto, Nigeria: Compiled report of chemical composition analyses of raw camel urine samples from some camels - Dogondaji, Rabiu A.; Wasagu, R.S.U.; Dr. Surajo Umar (PSM Biological Research, 2023)
This study was conducted to ascertain the nutritional level of camel urine in view of its incessant human oral consumption; albeit with a motive. Raw urine samples (U1-U5) from five domesticated female camels (Camelus dromedarius) at Kwakwalawa village of Sokoto; Sokoto State, Nigeria, were collected and analyzed for its proximate composition using standard methods. Samples were obtained overnight in April and May 2022 by skilled camel attendants whom placed open, sterilized plastic containers beneath whenever those camels were urinating. The results of the analyses based on percentage (w/v) showed 5.4 as total dissolved solids (TDS), 96.3 as moisture, 0.3 is ash, 0.1 as crude proteins, and 0.3 as crude carbohydrates, respectively. Conclusively, the analyzed samples of raw camel urine showed a surprising nutrient quality based on proximate composition.